Research on the upgrading of China’s regional industrial structure based on the perspective of green finance - Kong, Haojia; Xu, Yun; Zhang, Ruizhe; Tang, Decai; Boamah, Valentina; Wu, Guangliang; Zhou, Biao (Frontiers in Environmental Science, 2023)
This paper uses panel data from 30 Chinese provinces and cities from 2009 to 2019 to explore the mechanisms of green finance on industrial structure in China through panel regression and mediating effect models. The findings show regional heterogeneity in green finance and industrial structure in China. The level of green finance is high in both the eastern and central regions. Still, the industrial structure in the eastern region is the most balanced and reasonable, and the results show that the consistency between industrial structure and green finance development is stronger in the eastern region of China. The study of the mechanism of action of green finance by the intermediation effect model shows an overall mechanism of action of green finance in China to influence the upgrading of industrial structure through the financial sector. Still, it is shown as not strong partial intermediation, and the direct effect of green finance on the industrial structure is more obvious. In the analysis of regional heterogeneity, the mediating role of the financial sector is absent in the eastern and western regions, and other mediating variables that may be more significant are present. In contrast, the central region shows a masking effect. The findings suggest that in the development of green finance to restructure the industry, attention should be paid to the important role of financial institutions, especially in the central region where both green finance and industrial structure are at an intermediate level. Each region should adjust its industrial structure according to the time and place and promote upgrading of industrial structure.